Diverse changes in microglia morphology and axonal pathology during the course of 1 year after mild traumatic brain injury in pigs. (7th May 2021) - Grovola, Michael R.; Paleologos, Nicholas; Brown, Daniel P.; Tran, Nathan; Wofford, Kathryn L.; Harris, James P.; Browne, Kevin D.; Shewokis, Patricia A.; Wolf, John A.; Cullen, D. Kacy; Duda, John E.
Abstract: Over 2.8 million people experience mild traumatic brain injury (TBI) in the United States each year, which may lead to long‐term neurological dysfunction. The mechanical forces that are caused by TBI propagate through the brain to produce diffuse axonal injury (DAI) and trigger secondary neuroinflammatory cascades. The cascades may persist from acute to chronic time points after injury, altering the homeostasis of the brain. However, the relationship between the hallmark axonal pathology of diffuse TBI and potential changes in glial cell activation or morphology have not been established in a clinically relevant large animal model at chronic time points. In this study, we assessed the tissue from pigs subjected to rapid head rotation in the coronal plane to generate mild TBI. Neuropathological assessments for axonal pathology, microglial morphological changes, and astrocyte reactivity were conducted in specimens out to 1‐year post‐injury. We detected an increase in overall amyloid precursor protein pathology, as well as periventricular white matter and fimbria/fornix pathology after a single mild TBI. We did not detect the changes in corpus callosum integrity or astrocyte reactivity. However, detailed microglial skeletal analysis revealed changes in morphology, most notably increases in the number of microglial branches, junctions, and endpoints. These subtle changes were most evident in periventricular white matter and certain hippocampal subfields, and were observed out to 1‐year post‐injury in some cases. These ongoing morphological alterations suggest persistent change in neuroimmune homeostasis. Additional studies are needed to characterize the underlying molecular and neurophysiological alterations, as well as potential contributions to neurological deficits. Abstract : In this study, pigs were subjected to mild TBI by rapid head rotation and neuropathologically assessed for axonal pathology, microglial morphological changes, and astrocyte reactivity out to one year post injury. We detected acute changes in axonal pathology, particularly in the periventricular white matter and fimbria/fornix, as well as changes to microglia morphology in the periventricular white matter and hippocampal subfields out to one year post injury. These ongoing morphological alterations suggest persistent changes in neuroimmune homeostasis after a single mild TBI.